2003
DOI: 10.1002/arch.10090
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a cDNA encoding for a lysozyme from the gut of the reduviid bug Triatoma infestans

Abstract: We have isolated and characterised a Triatoma infestans cDNA encoding a lysozyme. A 174-bp fragment was amplified by PCR using degenerate oligodeoxyribonucleotide primers derived from the known amino acid sequences of lysozyme from other insects. This PCR fragment was used to screen a cDNA gut library of T. infestans. A clone containing the 3'-end of the lysozyme cDNA (219 bp) was isolated and sequenced. RACE was used to amplify the 5'-end of the lysozyme cDNA. After sequencing the complete lysozyme cDNA, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 38 publications
2
76
0
Order By: Relevance
“…The passage of the blood from the stomach to the digesting small intestine causes considerable destruction of symbiont populations, and only about 0,01% of the total population is still present in the rectum. 3 Since this development can not be correlated to the activity of lysozyme we are investigating other antibacterial compounds, e.g., defensins.…”
Section: Ve9 -Isolation and Characterization Of Defensin An Antimicrmentioning
confidence: 99%
See 4 more Smart Citations
“…The passage of the blood from the stomach to the digesting small intestine causes considerable destruction of symbiont populations, and only about 0,01% of the total population is still present in the rectum. 3 Since this development can not be correlated to the activity of lysozyme we are investigating other antibacterial compounds, e.g., defensins.…”
Section: Ve9 -Isolation and Characterization Of Defensin An Antimicrmentioning
confidence: 99%
“…The expression pattern of the lysozyme gene in the digestive tract of the bugs at different molting and feeding stages showed that this gene was upregulated directly after the molt and after feeding. 3 Investigating the expression of lysozymes in all parts used for activity tests via PCR amplification with specific lysozyme-primers, we obtained DNA-fragments by using cDNA of cardia, stomach, the final part of the small intestine and the salivary glands D2 and D3. Sequencing indicated that different lysozymes are expressed in the gut and salivary glands.…”
Section: Ve11 -Lysozymes Of Triatoma Infestansmentioning
confidence: 99%
See 3 more Smart Citations